Study of socio-demographic profile and contraceptive use among married women attending an Urban Health Centre, Berhampur - Padhy, Sarmistha; Nayak, Ranjeeta; Tripathy, R.M. (International Journal of Medical Research and Review, 2016)
Introduction: The higher fertility in India is attributed to early marriage, low level of literacy, poor level of living, limited use of contraceptives and traditional ways of life. Family planning plays a key role in deciding the desired family size and effective limitation of fertility. Objectives: 1) To study the socio-demographic profile of married women of reproductive age group attending anganwadi centres 2) To assess knowledge and practice of contraception among them 3) To find out the unmet need of contraception. Materials and Methods: A cross sectional study was conducted from May to July 2014 among married females between 15-45 years attending any of the six Anganwadi centres under the Urban Health Centre, Ankuli, Berhampur. 224 participants were interviewed in local language using a predesigned and pretested questionnaire. Results: 58.58% of the women were between 20-30 years and lived in nuclear families (65.6%). 29% had history of induced abortion. Most common reason of induced abortion were cited as unintended pregnancy (48.45) followed by complete family size (37.8%). Awareness about OCPs and female sterilisation was 96.9% followed by Condom (90.3%). Major source of information on contraception were through friends and relatives (47.5%) followed by husband (41.4%). Contraception was practiced by 48% of the respondents. Majority of them (26.8%) were OCP users followed by condom (8%). Use of contraception was mutually decided by the couples (99%). The unmet need of contraception was found to be 34.3%. Conclusion: Awareness about contraceptives is not sufficient for its actual use in this community for which new ways of motivating people to adopt and sustain family planning methods should be considered.